Leveraged Bubbles - Òscar Jordà; Moritz Schularick; Alan M. Taylor (Center for Economic Studies and ifo Institute (CESifo), 2015)
What risks do asset price bubbles pose for the economy? This paper studies bubbles in housing and equity markets in 17 countries over the past 140 years. History shows that not all bubbles are alike. Some have enormous costs for the economy, while others blow over. We demonstrate that what makes some bubbles more dangerous than others is credit. When fueled by credit booms, asset price bubbles increase financial crisis risks; upon collapse they tend to be followed by deeper recessions and slower recoveries. Credit-financed housing price bubbles have emerged as a particularly dangerous phenomenon.
Keywords: C14; C32; E44; E51; G01; N10; N20; 330; boom; bust; bank lending; debt overhang; crises; local projections